Listening to Student Voices in the Digital Sphere: A Tabayyun-Based Transformational Leadership Approach to Managing Learning Quality at State Vocational High School SMK Negeri 1 Pedan - Khomsatun Widhi Hastuti; Hery Setiyatna (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to analyze the meaning of student criticism in digital spaces as a source of quality data, the implementation of digital tabayyun ethics in conflict resolution, and transformational leadership practices in restoring a culture of learning quality. Using a qualitative approach with a descriptive-analytical case study design with an insider research scheme, this study positions the researcher as the main instrument and the Vice Principal for Quality Management at SMK Negeri 1 Pedan in 2025. Data were collected through semi-structured interviews, participant observation, and digital documentation, which were then analyzed using the circular model of Miles, Huberman, and Saldaña. The results of the study show three essential findings. First, student criticism and insults in private WhatsApp Group spaces are organic indicators of learning discomfort rooted in five formal learning anomalies. Second, transformational leadership in quality management supported by the Principal successfully mitigated relational conflicts through the orchestration of cross-sectoral digital tabayyun (Homeroom Teachers and Guidance Counselors) that was humanistic and persuasive, thereby fostering students' ethical awareness without a rigid punitive approach. Third, the restoration of a culture of quality was institutionalized through In-House Training (IHT)